Analysis of inorganic contaminants in Hoplias aimara Valenciennes 1846 (Trairão) explored by the fishing activity in the high Rio Araguari, Amapá, Brazil - Luz, Edilena Oliveira; Oliveira, Antonio Ferreira de; Souza, Luiza Prestes; Oliveira, Netiê Izabel da Silva; Perrone, Elis Lima; Bezerra, Roberto Messias; Florentino, Alexandro Cezar (Ciência e Natura, 2019)
This study aims to evaluate the concentration of inorganic contaminants in Hoplias aimara Valenciennes 1846, coming from the upper Rio Araguari, State of Amapa.